NYSTAGMUS IN CHILDHOOD: A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Nystagmus is an involuntary rhythmic oscillation of the eyes that results in decreased visual acuity owing to the excessive motion of pictures on the retina. This is because nystagmus causes the eyes to move in a repetitive pattern. It is of the utmost importance to differentiate infantile nystagmus from acquired nystagmus. In order to accomplish this, it is necessary to take into consideration not only the time at which the nystagmus first appeared, but also the features of its waveform. Oscillations of the eyes that are involuntary, often conjugate, and frequently rhythmic are referred to as nystagmus. Infantile nystagmus syndrome (INS) is the condition that accounts for the majority of cases of nystagmus in children. Because this ailment can last a person's entire life, it is essential that they are familiar with all of the treatment choices that are at their disposal. The primary foci of this review are the underlying etiology of nystagmus, the psychosocial and functional implications of nystagmus, and the current methods of treatments, which include optical, pharmacological, surgical, and rehabilitative treatment approaches. At this time, the brain mechanisms that are responsible for INS are not completely known. The evidence is limited to mostly pre- and post-study designs, and there are few objective comparisons of treatment procedures. The treatment choices are meant to increase the foveation length or correct abnormal head positions. Individualized management of INS should be implemented. The patient and the patient's physician are the ones who should make the decision regarding which treatment will be most beneficial for the patient in question.